1995
DOI: 10.1111/j.1476-5381.1995.tb16352.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of rabbit platelets by Ca2+ influx and thromboxane A2 release in an external Ca2+‐dependent manner by zooxanthellatoxin‐A, a novel polyol

Abstract: Zooxanthellatoxin‐A (ZT‐A), a novel polyhydroxylated long chain compound, isolated from a symbiotic marine alga Simbiodinium sp., caused aggregation in rabbit washed platelets in a concentration‐dependent manner (1–4 μM), accompanied by an increase in cytosolic Ca2+ concentration ([Ca2+]i). ZT‐A did not cause platelet aggregation or increase [Ca2+]i in a Ca2+‐free solution, and Cd2+ (0.1‐1 mM), Co2+ (1–10 mM) and Mn2+ (1–10 mM) inhibited ZT‐A‐induced aggregation. SK&F96365 (1–100 μM), a receptor operated Ca2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Vasoconstrictive activity was only seen with the macrolactone congeners ZTs and ZAD‐Cs, which indicated that the huge macrolactone structures were important for their activity. Furthermore, ZT‐A ( 23 ) caused aggregation in rabbit washed platelets, accompanied by an increase in the cytosolic Ca 2+ concentration 49. Thus, this potent voltage‐dependent Ca 2+ channel‐opening activity may be a common feature of symbiodinolide ( 1 ) and ZTs, and may be intimately involved in such constrictive activity.…”
Section: Symbiodinolide a Novel Polyol Macrolide That Activates N‐tymentioning
confidence: 99%
“…Vasoconstrictive activity was only seen with the macrolactone congeners ZTs and ZAD‐Cs, which indicated that the huge macrolactone structures were important for their activity. Furthermore, ZT‐A ( 23 ) caused aggregation in rabbit washed platelets, accompanied by an increase in the cytosolic Ca 2+ concentration 49. Thus, this potent voltage‐dependent Ca 2+ channel‐opening activity may be a common feature of symbiodinolide ( 1 ) and ZTs, and may be intimately involved in such constrictive activity.…”
Section: Symbiodinolide a Novel Polyol Macrolide That Activates N‐tymentioning
confidence: 99%
“…This leads to a cascade of reactions involving the release of calcium, the activation of calmodulin, protein kinase C (PKC) and phospholipase A 2 , ultimately leading to TXA 2 biosynthesis [58,59], the release of agranules [33] and surface glycoprotein expression.…”
Section: Molecular Mechanisms Intracellular Signaling and Calcium Homentioning
confidence: 99%
“…In addition, the depletion of intracellular Ca 2+ stores initiates activation of a so called capacitative Ca 2+ entry [7,8]. Both, intracellular Ca 2+ release and capacitative Ca 2+ entry increase free intracellular Ca 2+ concentration [Ca 2+ ]; and induce platelet aggregation by stimulation of the thromboxane A 2 biosynthesis [9]. In platelets from diabetic patients, increased intracellular Ca 2+ response was reported [10].…”
mentioning
confidence: 99%